Bibframe advances in 2016: Perspectives of the new bibliographic model - Agenjo-Bullón, Xavier; Hernández-Carrascal, Francisca (Anuario ThinkEPI, 2017)
The progress of the Bibframe Initiative in 2016 and the first quarter of 2017 is discussed. The difficulty of transforming the MARC 21 format into a new format lies within the model itself, but also in building a new cataloging ecosystem, both for catalogers and for library software. In spite of this, some of the most important libraries in the world are determined to follow this path. An analogy is drawn with the theoretical model and the subsequent cataloging rules promoted by IFLA, paying attention to the transition from AACR2 and ISBD to RDA, and from the FRBR family to LRM. The advantages that derive from the adoption of a data model adapted to RDA and linked open data are emphasized. OCLC, participating in the Bibframe initiative, has also explored the application of linked open data based on Schema.org. It is reported that the new version of the Bibframe 2.0 vocabulary has already been approved. And, finally, in 2107, the publication of new specifications to transform MARC 21 records to Bibframe will serve as an extension of the knowledge of this new standard.
Keywords: Bibframe; RDA; LRM; Schema.org; MARC 21 to Bibframe 2.0 conversion specifications.